PELATIHAN, MOTIVASI, DISIPLIN KERJA SEBAGAI MODEL DALAM MENINGKATKAN KINERJA KARYAWAN PERUSAHAAN DI WILAYAH KABUPATEN PASURUAN - Hariyanto, Hariyanto (DINAMIKA DOTCOM, 2017)
The development of planned and sustainable human resources is an absolute necessity especially for the future of the company. The purpose of this research is: to know the variable of motivation to performance, training variable to employee performance, motivation variable to work discipline, training variable to work discipline and motivation have influence to employee performance through work discipline and job training variable have influence to employee performance. The results show that all pathways have a significant influence. For that BKBPM Malang more attention to the quality of softskill themselves, both in knowledge and skills that lead to more useful in implementing the program of adolescent PIK.Keywords: Motivation, Dicipline, performance